After compensating the bistatic deformation phase term, we transform Eq. (26) into a range-Doppler domain and obtain the expression as Display Formula
$g(t,f\tau )=\sigma p\u2009exp[\u2212j2\pi c(rOTDT+rORDR)f0]exp[\u2212j2\pi (B\xb7\tau OT+E\xb7\tau OR)f0]\xb7exp[\u2212j2\pi (A\xb7\tau OT+D\xb7\tau OR)f\tau ]exp{j\pi km[t\u2212R(f\tau )c]2},$(29)
where Display Formula$A=RRcvT2\u2009cos2\u2009\theta TcRTcvR2\u2009cos2\u2009\theta Rc+RRcvT2\u2009cos2\u2009\theta Tc,$(30)
Display Formula$B=vT(RTcvR2\u2009cos2\u2009\theta Rc\u2009sin\u2009\theta Tc\u2212RRcvTvR\u2009cos2\u2009\theta Tc\u2009sin\u2009\theta Rc)c(RTcvR2\u2009cos2\u2009\theta Rc+RRcvT2\u2009cos2\u2009\theta Tc),$(31)
Display Formula$D=RTcvR2\u2009cos2\u2009\theta RcRTcvR2\u2009cos2\u2009\theta Rc+RRcvT2\u2009cos2\u2009\theta Tc,$(32)
Display Formula$E=vR(RRcvT2\u2009cos2\theta Tc\u2009sin\u2009\theta Rc\u2212RTcvTvR\u2009cos2\u2009\theta Rc\u2009sin\u2009\theta Tc)c(RTcvR2\u2009cos2\u2009\theta Rc+RRcvT2\u2009cos2\u2009\theta Tc),$(33)
Display Formula$\mu T1=A\xb7cf\tau f0vT+B\xb7cvT\mu T2=B\xb7cvT,$(34)
Display Formula$\mu R1=D\xb7cf\tau f0vR+E\xb7cvR\mu R2=E\xb7cvR,$(35)
Display Formula$DT=1\u2212\mu T12DR=1\u2212\mu R12.$(36)